Preparation method of double-layer positive electrode cylindrical battery

By using a double-layer positive electrode sheet composed of large and small positive electrode active materials in lithium-ion batteries, and combined with pulsed to form an interface film, the problem of interface concentration polarization in lithium-ion batteries is solved, and the battery performance and cycle life are significantly improved.

CN119581689AInactive Publication Date: 2025-03-07YANTAI LIHUA ELECTRIC POWER TECHNOLOGY CO LTD
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202411663579.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-20
Publication Date
2025-03-07
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

In high-nickel ternary material lithium-ion batteries, the lithium ion concentration polarization phenomenon at the interface leads to a bottleneck for improved battery performance, affecting energy density, cycle stability and safety.

Method used

A double-layer positive electrode sheet composed of large and small positive electrode active materials is used to combine with pulses to form an inorganic-rich interface film to reduce interface resistance and concentration polarization.

Benefits of technology

It significantly reduces the energy loss caused by concentration polarization, improves the battery's performance in a high-rate charging and discharging environment, and ensures the maintenance and even prolongs the battery cycle life.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119581689A_ABST
    Figure CN119581689A_ABST
Patent Text Reader

Abstract

The invention discloses a preparation method of a double-layer positive electrode cylindrical battery, which comprises the following steps: step 1, selecting two positive electrode active materials with different particle sizes, respectively preparing large-particle slurry and small-particle slurry, coating at least one side surface of a current collector with the large-particle slurry, and drying to obtain a lower electrode layer, coating small-particle slurry on one side, far away from the current collector, of the lower motor layer, drying to obtain an upper electrode layer, and rolling to obtain a positive pole piece; 2, winding the positive pole piece, the diaphragm and the negative pole piece to form a battery cell, respectively welding the positive end and the negative end of the battery cell with a collector plate, putting the welded battery cell into a shell, and welding the shell; and step 3, injecting an electrolyte, standing and infiltrating, and performing pulse formation. The lithium ion battery has the beneficial effects that the energy loss caused by concentration polarization is reduced and the high-rate charge-discharge performance of the battery is improved by combining the double-layer positive pole piece consisting of the positive active materials with large and small particles and the interfacial film which is rich in inorganic matters and is formed by pulse formation.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of cylindrical batteries, and in particular to a method for preparing a double-layer positive electrode cylindrical battery. Background Art

[0002] With the development of electric vehicles, portable electronic devices and energy storage systems, the demand for high-performance lithium-ion batteries is also growing. At present, in order to improve the energy density of lithium-ion batteries, high-nickel ternary materials are used, such as NCM811, because of its high nickel content, it can provide higher specific capacity, thereby significantly improving the energy density of the battery. However, under high-rate charge and discharge conditions, especially when pursuing higher energy density and thicker electrode design, the lithium ion concentration polarization phenomenon at the interface has become a bottleneck restricting the further improvement of lithium-ion battery performance. Concentration polarization not only leads to an increase in the internal resistance of the battery and reduces the charge and discharge efficiency, but may also accelerate the aging process of the battery and affect the cycle stability and safety.

[0003] In order to deal with the interfacial concentration polarization phenomenon, researchers have explored a variety of traditional strategies. First, optimizing the electrolyte formula is a common method, which aims to improve the solvation structure and transport characteristics of lithium ions by adjusting the ratio of solvents and solutes and adding specific additives. However, this method needs to find a balance between electrolyte performance and cost. Especially for high-nickel ternary materials, special attention should be paid to the stability of the electrolyte. Secondly, improving the utilization rate of active substances is also an effective means to reduce concentration polarization. By improving the electrode preparation process and structural design, such as increasing the contact area between the active substance and the electrolyte, the efficiency of lithium ion insertion and extraction can be significantly improved. However, this method is often accompanied by the complexity of the electrode structure, increased manufacturing costs, and may introduce new interface problems. Furthermore, surface modification technology changes the surface properties of the electrode material by coating a thin film or chemical treatment, improves its compatibility with the electrolyte, and thus reduces the interface resistance and concentration polarization. Although the effect is significant, this method may change the intrinsic properties of the electrode material, affect the overall performance of the battery, and the process control is relatively complex. In addition, designing more efficient lithium ion transmission paths, such as constructing three-dimensional porous electrode structures or using nanoscale electrode materials, aims to increase the transmission channels of lithium ions and shorten the diffusion paths. However, these methods introduce complex processes in the preparation of electrode materials and battery assembly, increasing manufacturing costs and difficulties. It can be seen that although traditional methods of reducing interfacial concentration polarization have their own advantages, they all have limitations when applied to high-nickel ternary materials, especially in the context of pursuing higher energy density and thicker electrode design. Summary of the invention

[0004] The purpose of the present invention is to overcome the shortcomings of the prior art and provide a method for preparing a double-layer positive cylindrical battery. By using a double-layer positive electrode sheet composed of large-particle and small-particle positive electrode active materials, combined with an inorganic-rich interface film formed by pulse formation, the energy loss caused by concentration polarization is reduced, and the performance of the battery in a high-rate charge and discharge environment is improved, so that it can quickly respond to charge and discharge requirements, while ensuring that the battery cycle life is maintained or even extended.

[0005] The object of the present invention is achieved by the following technical measures: A method for preparing a double-layer positive electrode cylindrical battery comprises the following steps:

[0006] Step 1, select two positive electrode active materials with different particle sizes, and prepare large particle slurry and small particle slurry respectively, apply the large particle slurry on at least one side of the current collector, and obtain the lower electrode layer after drying, apply the small particle slurry on the side of the lower electrode layer away from the current collector, and obtain the upper electrode layer after drying, and obtain the positive electrode sheet after rolling;

[0007] Step 2: Wind the positive electrode sheet, the separator and the negative electrode sheet into a battery cell, weld the positive terminal and the negative terminal of the battery cell to the collector plate respectively, put the welded battery cell into the shell and weld the shell;

[0008] Step 3: Inject electrolyte, let it stand and soak, and pulse form.

[0009] In some embodiments, the positive electrode active material is NCM811.

[0010] In some embodiments, the large particles have a particle size of 5-20 μm, and the small particles have a particle size of 1-5 μm.

[0011] In some embodiments, the thickness ratio of the upper electrode layer to the lower electrode layer is 2-3.

[0012] In some embodiments, the large particle slurry and the small particle slurry both include a conductive agent, a binder, and a solvent.

[0013] In some embodiments, the drying temperature after coating of the large particle slurry is 60-100° C., and the drying time is 5-20 min.

[0014] In some embodiments, the drying temperature of the small particle slurry after coating is 80-120° C., and the drying time is 10-30 min.

[0015] In some embodiments, the temperature of the static infiltration is 45° C. and the time is 24 hours.

[0016] In some embodiments, the pulse formation method includes charging at a current of 0.05C for 30 seconds, then standing for 30 seconds, and repeating the cycle until the battery reaches its upper charging limit voltage.

[0017] Compared with the prior art, the beneficial effects of the present invention are as follows: the present invention reduces the energy loss caused by concentration polarization through a double-layer positive electrode sheet composed of large-particle and small-particle positive electrode active materials, combined with an inorganic-rich interface film formed by pulse formation, and further improves the performance of the battery under high-rate charge and discharge conditions, enabling it to respond quickly to charge and discharge requirements, while ensuring that the battery cycle life is maintained or even extended. This allows batteries using thick electrodes to maintain higher energy output and a more stable voltage platform even under harsh conditions of high-rate charge and discharge, perfectly meeting the urgent needs for high-performance batteries in high-end fields such as electric vehicles and energy storage systems.

[0018] The present invention is described in detail below with reference to the accompanying drawings and specific embodiments. BRIEF DESCRIPTION OF THE DRAWINGS

[0019] Figure 1 It is a schematic diagram of the microstructure of the upper electrode layer and the lower electrode layer.

[0020] Figure 2 It is a schematic diagram of the structure of a double-layer positive electrode.

[0021] Figure 3 This is the SEM image of the double-layer positive electrode.

[0022] Figure 4 This is a comparison chart of the rate performance of double-layer positive electrode cylindrical batteries and single-layer positive electrode cylindrical batteries.

[0023] Figure 5 This is a comparison chart of the cycle performance of double-layer positive electrode cylindrical batteries and single-layer positive electrode cylindrical batteries. DETAILED DESCRIPTION

[0024] A method for preparing a double-layer positive electrode cylindrical battery comprises the following steps:

[0025] Step 1, preparation of double-layer positive electrode sheet: Specifically, the preparation of double-layer positive electrode sheet includes preparation of large particle slurry and small particle slurry; coating and drying of lower electrode layer; coating and drying of upper electrode layer; and roll forming.

[0026] Preparation of large particle slurry and small particle slurry:

[0027] Two positive electrode active materials with different particle sizes are selected and prepared into large particle slurry and small particle slurry respectively.

[0028] In some embodiments, NCM811 is selected as the positive electrode active material.

[0029] In some embodiments, the particle size of the large particles is 5-20 μm, and the particle size of the small particles is 1-5 μm. Preferably, the particle size of the large particles is 10 μm, and the particle size of the small particles is 3 μm.

[0030] In some embodiments, the large particle slurry and the small particle slurry both include a conductive agent, a binder and a solvent. Preferably, the conductive agent includes SP and CNT, the binder includes one or more of PVDF and SBR, and the solvent includes NMP.

[0031] The specific preparation method of large particle slurry and small particle slurry includes: mixing large particle positive electrode active material / small particle positive electrode active material with conductive agent and binder in proportion, adding appropriate amount of solvent, and stirring with a stirrer until a uniform and fine slurry is formed.

[0032] Coating and drying of the lower electrode layer:

[0033] The large particle slurry is coated on at least one side of the current collector, and the lower electrode layer is obtained after drying.

[0034] In some embodiments, the current collector is aluminum foil.

[0035] In some embodiments, the drying temperature after the large particle slurry is coated is 60-100°C, preferably 80°C, and the drying time is 5-20 minutes, and the specific drying time depends on the thickness of the slurry and the drying equipment. The current collector coated with the large particle slurry is preliminarily dried at a set temperature to remove excess solvent and form a preliminarily solidified lower electrode layer.

[0036] Coating and drying of the upper electrode layer:

[0037] The small particle slurry is coated on the side of the lower motor layer away from the current collector, and the upper electrode layer is obtained after drying.

[0038] In some embodiments, the drying temperature after the small particle slurry is coated is 80-120°C, preferably 100°C, and the drying time is 10-30 minutes, and the specific drying time depends on the slurry thickness and the drying equipment. The current collector coated with the double-layer positive electrode slurry is secondary dried at a higher temperature to ensure that the two layers of electrode materials are tightly combined to form a stable double-layer positive electrode structure.

[0039] Roll forming:

[0040] The dried double-layer positive electrode sheet is rolled to remove excess pores and bubbles, so that the two layers of electrode materials are more tightly combined. The pressing pressure is controlled within 10-20Mpa to avoid damage to the electrode structure. The pressed double-layer positive electrode sheet is cut, punched and other forming processes are performed to obtain a positive electrode sheet that meets the requirements.

[0041] In some embodiments, the thickness ratio of the upper electrode layer to the lower electrode layer is 2-3.

[0042] The double-layer positive electrode plate of the present invention integrates the synergistic mechanism of the upper small particles and the lower large particles. The upper small particles achieve rapid lithium ion transmission with their excellent lithium ion response speed; while the lower large particles ensure the high energy density of the battery with their excellent capacity performance.

[0043] Step 2, assembly of double-layer positive cylindrical battery: the positive electrode sheet, separator and negative electrode sheet are wound into a battery cell, the positive terminal and negative terminal of the battery cell are welded to the collecting plate respectively, the welded battery cell is placed as a whole into the shell and the shell is welded.

[0044] In some embodiments, the negative electrode plate includes one of a graphite negative electrode plate, a silicon carbon (Si) negative electrode plate, and a lithium titanate (LTO) negative electrode plate.

[0045] Step 3, double-layer positive cylindrical battery injection and formation: After the battery assembly is completed, the assembled cylindrical battery is placed at 45°C for 24 hours to dry, and an injection operation is performed through the positive electrode side injection port to inject the electrolyte into the battery. The injection coefficient is preferably 2.5g / Ah, and then it is allowed to soak to allow the electrolyte to fully soak the electrode material. After soaking, the double-layer positive cylindrical battery is pulse-formed. After the formation is completed, the battery is placed at 45°C for aging, and finally the positive electrode side is welded and sealed with a sealing sheet.

[0046] In some embodiments, the temperature of the static infiltration is 45° C. and the time is 24 hours.

[0047] In some embodiments, the pulse formation method includes charging at a current of 0.05C for 30 seconds, then standing for 30 seconds, and repeating the cycle until the battery reaches its upper charging voltage limit. At the interface of lithium-ion batteries, the rate of electron gain and loss is significantly faster than the migration rate of lithium ions, which makes it difficult for lithium ions to complete the desorption / embedding process in the positive electrode active material in time, resulting in excessive "accumulation" of electrons inside the positive electrode active material. This excessive "accumulation" of electrons will cause the open circuit voltage of the battery to quickly cross the decomposition voltage interval of the additive. In the pulse charging mode, by periodically introducing a standing stage, the excessive "accumulation" of electrons in the positive electrode material can be greatly reduced, so that the open circuit voltage of the battery can be maintained within the decomposition voltage interval of the additive for as long as possible. Therefore, the pulse charging method can significantly increase the content of inorganic components in the interface film and generate an interface film that effectively inhibits interface polarization. This interface film not only ensures the smooth transmission and uniform distribution of lithium ions on the interface, but also improves the transmission efficiency of lithium ions inside the thick electrode by matching the double-layer positive electrode structure, effectively avoiding the occurrence of interface concentration polarization.

[0048] In the early stage of charging, the small particles of NCM811 on the upper layer can quickly release lithium ions into the electrolyte due to their shorter lithium ion diffusion path, thereby forming a high concentration area locally. According to Fick's law, these high-concentration lithium ions can diffuse rapidly into the electrolyte, effectively avoiding the concentration polarization phenomenon caused by the excessive lithium ion concentration on the surface of the small particles. At the same time, although the large particles of NCM811 in the lower layer diffuse relatively slowly, due to the "buffer zone" formed by the small particles on the upper layer, the electrolyte concentration around it can be smoothly transitioned, thereby reducing the occurrence of overall concentration polarization. More importantly, an inorganic-rich interface film is also formed on the surface of the double-layer structure electrode during the pulse formation process. This interface film significantly reduces the concentration polarization during the cycle by increasing the diffusion rate of lithium ions at the interface, thereby improving the battery's rate performance.

[0049] When the battery enters the discharge stage, the small particles of NCM811 on the upper layer can receive lithium ions in the electrolyte faster and quickly embed them into the material, while maintaining a relatively stable concentration of lithium ions in the electrolyte. As the discharge progresses, the large particles on the lower layer gradually embed lithium ions, forming a concentration gradient from high to low. Since the small particles on the upper layer have efficient lithium ion exchange capabilities, the continuous supply of lithium ions in the electrolyte is ensured. The small particles are close to the coating layer of the large particles, and the lithium ion concentration near the small particles is higher, which can fully supplement the area with lower lithium ion concentration near the large particles, thereby improving the concentration polarization between the bulk electrolyte and the large particles. Combined with an inorganic-rich interface film, the concentration polarization phenomenon caused by the decrease in lithium ion concentration can be effectively reduced even in the later stages of discharge.

[0050] Example 1

[0051] This embodiment provides a method for preparing a double-layer positive electrode cylindrical battery, which is as follows:

[0052] Step 1, prepare a double-layer positive electrode sheet: select NCM811 with a particle size of 10μm and 3μm, the conductive agent is SP and CNT, the binder is PVDF, NCM811, SP, CNT and CNT are mixed in a ratio of 96:1:0.6:2.4, add 40wt% (relative to dry material) of solvent NMP, stir with a stirrer, the speed of the stirrer is 30r / min, until a uniform and fine slurry is formed, and 10μm NCM811 slurry and 3μm NCM811 slurry are prepared. Spray 10μm NCM811 slurry on one side of the aluminum foil with a coating thickness of 40μm, dry at 80°C for 15min, and obtain the lower electrode layer. Spray 3μm NCM811 slurry on the surface of the lower motor layer with a coating thickness of 100μm, and dry at 120°C for 15min to obtain the upper electrode layer. The roller pressing curing pressure is 10-20MPa, the hot roller temperature is 25°C, and the double-layer positive electrode sheet is prepared, such as Figure 1-3 As shown, ① is the upper electrode layer, ② is the lower electrode layer, and ③ is the aluminum foil. The pressed double-layer positive electrode sheet is subjected to cutting, punching and other forming processes to obtain a positive electrode sheet that meets the requirements.

[0053] Step 2, assemble cylindrical batteries: wind the positive electrode sheet formed in step 1, the 13μm separator (10um base film + 3μm ceramic coating), and the graphite negative electrode sheet into a battery cell, weld the positive and negative terminals of the battery cell to the collecting plates respectively, put the welded battery cell as a whole into the shell and weld the shell.

[0054] Step 3: Injection and formation: Inject electrolyte into the cylindrical battery assembled in step 2. The electrolyte has a volume ratio of 1.0 mol·L -1 LiPF6+0.1mol·L -1 LiODFB in EC / DEC / EMC (1:1:1 vol%) was immersed at 45°C for 24 hours, then charged at 0.05C for 30 seconds, and then left to stand for 30 seconds, and the cycle was repeated until the battery reached its upper charging limit voltage.

[0055] Comparative Example 1

[0056] This comparative example provides a method for preparing a single-layer positive electrode cylindrical battery.

[0057] Preparation of single-layer positive electrode sheet: Select NCM811 with a particle size of 10μm, SP and CNT as conductive agents, PVDF as binder, NCM811, SP, CNT and CNT in a ratio of 96:1:0.6:2.4, add 40wt% solvent NMP, stir with a stirrer at a speed of 30r / min until a uniform and fine slurry is formed, and prepare 10μm NCM811 slurry. Spray 10μm NCM811 slurry on one side of the aluminum foil with a coating thickness of 140μm, dry at 120°C for 15min, and obtain a single-layer electrode layer. The roller curing pressure is 10-20MPa, and the hot roller temperature is 25°C to prepare a single-layer positive electrode sheet. The pressed single-layer positive electrode sheet is cut, punched and other forming processes are performed to obtain a positive electrode sheet that meets the requirements.

[0058] The assembly process of the cylindrical battery is the same as that in Example 1.

[0059] Injection and formation of cylindrical battery: inject electrolyte into the cylindrical battery assembled in step 2. The electrolyte is 1.0 mol·L -1 LiPF6+0.1mol·L -1 LiODFB in EC / DEC / EMC (1:1:1 vol%) was kept at 45°C for 24 h and then charged to the upper limit voltage at a constant current of 0.05 C.

[0060] The performance of the cylindrical batteries in the above embodiments and comparative examples was tested.

[0061] Battery rate test: The battery is tested at 0.1C, 0.2C, 0.5C, 1C, 2C, and 5C currents. The test results are as follows: Figure 4 shown.

[0062] Battery cycle test: The battery is cycled at a current of 1C. The test results are as follows: Figure 5 shown.

[0063] By comparing the test results of Example 1 with those of Comparative Example 1, it can be seen that the battery rate and battery cycle performance of the double-layer positive electrode plate coated with large and small particles of NCM811 combined with a pulse formation method are significantly better than those of the single-layer cylindrical battery coated with a single particle size of NCM811 and a constant current formation method.

[0064] In the present invention, the terms "one embodiment", "some embodiments", "examples", "specific examples", or "some examples" etc. mean that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representations of the above terms do not necessarily refer to the same embodiment or example. Moreover, the described specific features, structures, materials or characteristics may be combined in any one or more embodiments or examples in a suitable manner. In addition, those skilled in the art may combine and combine the different embodiments or examples described in this specification and the features of the different embodiments or examples, without contradiction.

[0065] Although the above embodiments have been shown and described, it is to be understood that the above embodiments are exemplary and are not to be construed as limitations on the present invention. Changes, modifications, substitutions and variations of the above embodiments by those of ordinary skill in the art are all within the scope of protection of the present invention.

Claims

1. A method for preparing a double-layer positive electrode cylindrical battery, characterized in that: The following steps are involved: Step 1, select two positive electrode active materials with different particle sizes, and prepare large particle slurry and small particle slurry respectively, apply the large particle slurry on at least one side of the current collector, and obtain the lower electrode layer after drying, apply the small particle slurry on the side of the lower electrode layer away from the current collector, and obtain the upper electrode layer after drying, and obtain the positive electrode sheet after rolling; Step 2: Wind the positive electrode sheet, the separator and the negative electrode sheet into a battery cell, weld the positive terminal and the negative terminal of the battery cell to the collector plate respectively, put the welded battery cell into the shell and weld the shell; Step 3: Inject electrolyte, let it stand and soak, and pulse form.

2. The method for preparing a double-layer positive electrode cylindrical battery according to claim 1, characterized in that: The positive electrode active material is NCM811.

3. The method for preparing a double-layer positive cylindrical battery according to claim 1 or 2, characterized in that: The particle size of the large particles is 5-20 μm, and the particle size of the small particles is 1-5 μm.

4. The method for preparing a double-layer positive electrode cylindrical battery according to claim 1, characterized in that: The thickness ratio of the upper electrode layer to the lower electrode layer is 2-3.

5. The method for preparing a double-layer positive electrode cylindrical battery according to claim 1, characterized in that: The large particle slurry and the small particle slurry both include a conductive agent, a binder and a solvent.

6. The method for preparing a double-layer positive electrode cylindrical battery according to claim 1, characterized in that: The drying temperature of the large particle slurry after coating is 60-100° C., and the drying time is 5-20 minutes.

7. The method for preparing a double-layer positive electrode cylindrical battery according to claim 1, characterized in that: The drying temperature of the small particle slurry after coating is 80-120° C., and the drying time is 10-30 minutes.

8. The method for preparing a double-layer positive electrode cylindrical battery according to claim 1, characterized in that: The temperature of the static soaking is 45° C. and the time is 24 hours.

9. The method for preparing a double-layer positive electrode cylindrical battery according to claim 1, characterized in that: The pulse formation method includes charging at a current of 0.05C for 30 seconds, then standing for 30 seconds, and repeating the cycle until the battery reaches its upper charging limit voltage.

Citation Information

Patent Citations

  • Formation and matching method for lithium ion battery

    CN107293812A

  • Positive electrode for secondary battery method for preparing the same and secondary battery comprising the same

    CN108604674A

  • Lithium secondary battery

    CN111081993A

  • Positive electrode for secondary battery, method for manufacturing same and lithium secondary battery comprising same

    EP3396746A1

  • Positive electrode plate, lithium-ion secondary battery, vehicle, and battery loading device

    JP2009026599A